2022
DOI: 10.1038/s41598-022-07302-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of berry-based supplements and foods on cognitive function: a systematic review

Abstract: In the current decade, a growing body of evidence has proposed the correlation between diet and cognitive function or dementia in the ageing population. This study was designed to appraise discoveries from the randomized controlled trials to confirm the effects of berry-based supplements or foods on cognitive function in older adults. PubMed/MEDLINE, Cochrane Central Register of Controlled Trials, Web of Science, Scopus, EMBASE, Google Scholar, and ProQuest as well as SID, Magiran, and Iranmedex electronic dat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 119 publications
0
9
0
Order By: Relevance
“…In recent systematic reviews examining the impact of grape ( Bird et al, 2022 ) and blueberry ( Hein et al, 2019 ) administration on cognitive performance, it was concluded that there was some evidence of efficacy. Moreover, in a systematic review of berry-based supplements and foods, it was reported that they may have beneficial effects on resting brain perfusion, cognitive function, memory performance, executive functioning, processing speed, and attention indices ( Bonyadi et al, 2022 ). However, substantial differences in the clinical trials make robust conclusions difficult.…”
Section: Discussionmentioning
confidence: 99%
“…In recent systematic reviews examining the impact of grape ( Bird et al, 2022 ) and blueberry ( Hein et al, 2019 ) administration on cognitive performance, it was concluded that there was some evidence of efficacy. Moreover, in a systematic review of berry-based supplements and foods, it was reported that they may have beneficial effects on resting brain perfusion, cognitive function, memory performance, executive functioning, processing speed, and attention indices ( Bonyadi et al, 2022 ). However, substantial differences in the clinical trials make robust conclusions difficult.…”
Section: Discussionmentioning
confidence: 99%
“…The improved overall functioning, performance, and quality of life (OQ45.2 scores) may also be related to a reduction in the extra-GI symptoms that are prevalent in patients with FGID [ 5 ]. Several recent reviews have summarized the effects of blueberries or polyphenols in various formulations on musculoskeletal and cognitive function in different human cohorts, but effects in FGID have so far not been reported [ 13 , 15 , 45 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…These trials involve different study populations and may involve subjects with existing risk factors. The intake of berries or berry-based products may also have beneficial effects on cognitive function ( 56 , 57 ).…”
Section: Health Outcomes Relevant For Nordic and Baltic Countriesmentioning
confidence: 99%